A qualitative analysis of bifocusing method for a real-time anomaly detection in microwave imaging. (1st May 2023) - Kang, Sangwoo; Park, Won-Kwang; Son, Seong-Ho
Abstract: In this contribution, we consider the bifocusing method (BFM) for identifying small anomalies from scattering parameter data in microwave imaging. To this end, we design an imaging function of BFM and perform a qualitative analysis for the imaging function by establishing a relationship with the infinite series of Bessel functions of integer order, applied frequency, material properties, and the antenna arrangement. The revealed mathematical structure of the imaging function and simulation results with synthetic data show why BFM is fast and effective for identifying unknown anomalies in microwave imaging.